2011
DOI: 10.1016/j.ejogrb.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Serum estradiol does not differentiate stress, mixed and urge incontinent women around menopause. A report from the Women's Health in the Lund Area (WHILA) study

Abstract: Serum estradiol does not differentiate stress, mixed and urge incontinent women around menopause. A report from the Women's Health in the Lund Area (WHILA) study.Andrada, Maria; Källén, Karin; Lidfeldt, Jonas; Samsioe, Göran; Teleman, Pia General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Contrary to our findings, some studies showed that higher circulating oestrogen levels were associated with UI of any type [13,22]. Nevertheless, it should be noted that these studies included a mixed cohort of patients with incontinence and not specifically women with SUI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, some studies showed that higher circulating oestrogen levels were associated with UI of any type [13,22]. Nevertheless, it should be noted that these studies included a mixed cohort of patients with incontinence and not specifically women with SUI.…”
Section: Discussioncontrasting
confidence: 99%
“…The median (range) BMI in the SUI group was 26 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) kg/m 2 and 9/47 women in this group (19%) were classified as obese, 20/47 (43%) were overweight and 18/47 (38%) had a normal BMI. The mean (AESD) score on the Oxford grading scale was 2.35 (AE0.706) and first desire to void occurred at 208 (AE47.07) mL.…”
Section: Participant Characteristics In the Sui Groupmentioning
confidence: 99%
“…In the observational Women's Health in the Lund area study, 400 out of 2,221 postmenopausal women, aged 50–60 years old upon enrollment, reported incontinence symptoms. In 369 of these women in whom estradiol levels were available, no correlation between endogenous estradiol and incontinence in general or stress urinary incontinence in particular could be demonstrated …”
Section: Discussionmentioning
confidence: 95%
“…Aging and the menopause per se are associated with a progressive increase in the severity of UI and discomfort [28]. Despite this, serum estradiol has not been related to UI during the menopause transition [29,11], or with urodynamic parameters [30].…”
Section: Discussionmentioning
confidence: 98%
“…Despite this, several reports have failed to demonstrate that hormone therapy (HT) improves urinary symptoms (i.e. incontinence, urge syndrome) in postmenopausal women [7][8][9][10][11]. Important to state is that subjective sensation related to UI does not always correlate with urodynamic findings [12].…”
Section: Introductionmentioning
confidence: 95%